2012
DOI: 10.1111/j.1654-1103.2012.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotic homogenization of upland vegetation: patterns and drivers at multiple spatial scales over five decades

Abstract: Questions Is there evidence for biotic homogenization of upland vegetation? Do the magnitude and nature of floristic and compositional change vary between vegetation types? What can be inferred about the drivers responsible for the observed changes? Location Upland heath, mire and grassland communities of the northwest Highlands of Scotland, UK. Methods We re‐survey plots first described in a phytosociological study of 1956–1958 to assess the changes in plant species composition over the last 50 yr in five maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 77 publications
5
94
1
Order By: Relevance
“…Long-term homogenization of mountain vegetation at a regional scale has been attributed to both a warming climate and intensive grazing (Britton et al 2009;Ross et al 2012), whilst herbivory has been directly linked with community homogenization at the landscape scale (Austrheim & Eriksson 2001;Rooney 2009). In our study, we found only weak evidence in support of the grazing-homogenization hypothesis.…”
Section: H O M O G E N I Z a T I O Nmentioning
confidence: 99%
“…Long-term homogenization of mountain vegetation at a regional scale has been attributed to both a warming climate and intensive grazing (Britton et al 2009;Ross et al 2012), whilst herbivory has been directly linked with community homogenization at the landscape scale (Austrheim & Eriksson 2001;Rooney 2009). In our study, we found only weak evidence in support of the grazing-homogenization hypothesis.…”
Section: H O M O G E N I Z a T I O Nmentioning
confidence: 99%
“…Biotic homogenization is projected to have both ecological and evolutionary consequences, including an effect on ecosystem resilience to environmental perturbations (Olden, Poff, Douglas, Douglas & Fausch, 2004). The degree of homogenization varies across space (Olden, Poff & McKinney, 2006), and certain areas may be particularly susceptible due to a combination of biotic and abiotic factors (Olden & Poff, 2003; Ross, Woodin, Hester, Thompson & Birks, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Species abundance is of course also influenced by habitat availability and environmental change. In this context, it is noteworthy that over the past 50 years, Pleurozia purpurea has increased in several Scottish upland plant communities including dwarf shrub heaths, while Anastrophyllum has decreased where former heathland has become degraded (Ross et al, 2012).…”
Section: Species' Growth Rates and Field Abundancementioning
confidence: 99%